Statins augment the chemosensitivity of colorectal cancer cells inducing epigenetic reprogramming and reducing colorectal cancer cell 'stemness' via the bone morphogenetic protein pathway. Issue 11 (6th May 2011) - Kodach, Liudmila L; Jacobs, Rutger J; Voorneveld, Philip W; Wildenberg, Manon E; Verspaget, Henricus W; van Wezel, Tom; Morreau, Hans; Hommes, Daniel W; Peppelenbosch, Maikel P; van den Brink, Gijs R; Hardwick, James C H
Abstract : Background: Promoter hypermethylation is an important and potentially reversible mechanism of tumour suppressor gene silencing in cancer. Compounds that demethylate tumour suppressor genes and induce differentiation of cancer cells, but do not have toxic side effects, would represent an exciting option in cancer therapy. Statins are cholesterol-lowering drugs with an excellent safety profile and associated with a reduced incidence of various cancers including colorectal cancer (CRC). The authors have previously shown that statins act by activating tumour suppressive bone morphogenetic protein (BMP) signalling in CRC, increasing expression of BMP2. BMP2 is silenced by hypermethylation in gastric cancer. Aim: To investigate whether BMP2 is methylated in CRC, whether statins can reverse this, and what implications this has for the use of statins in CRC. Methods: Methylation-specific PCR, bisulphite sequencing, immunoblotting, reverse transcription PCR, quantitative PCR, fluorescence-activated cell sorting analysis, an in vitro DNA methyltransferase (DNMT) assay, and cell viability studies were performed on CRC cells. The effect of statins was confirmed in a xenograft mouse model. Results: BMP2 is silenced by promoter hypermethylation in cell lines with the hypermethylator phenotype and in primary tumours. Treatment with lovastatin downregulates DNMT activity, leading to BMP2 promoter demethylation and to upregulation of expression of BMP2 as well as other genes methylated in CRC. Statins alter gene expression, indicating a shift from a stem-like state to a more differentiated state, thereby sensitising cells to the effects of 5-fluorouracil. In a xenograft mouse model, simvastatin treatment induces BMP2 expression, leading to differentiation and reduced proliferation of CRC cells. Conclusions: Statins act as DNMT inhibitors, demethylating the BMP2 promoter, activating BMP signalling, inducing differentiation of CRC cells, and reducing 'stemness'. This study indicates that statins may be able to be used as differentiating agents in combined or adjuvant therapy in CRC with the CpG island methylator phenotype.